ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT SISWA MEMILIH JURUSAN IPS SE-KECAMATAN PASAR SUNGAI PENUH - Pratiwi Indah Sari, Annisa Indrianti, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to determine the description of factors that affect the interest of students in choosing the majors and factors considered in choosing the majors IPS Jenjang SMA Se-Kecamatan Pasar Sungai Penuh. The results showed that the internal factors that affect students in choosing the majors included in the category of 68.80% enter the category quite well, while external factors score 60.10% with good enough category. Meanwhile, to answer the factors that most affect students in choosing the department is the factor of student desire with a value of 0.959 and the second factor is experience with a value of 0.954.Kata Kunci : Department, Student Interest